2008
DOI: 10.1257/aer.98.5.1829
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for, and Impact of, Learning HIV Status

Abstract: This paper evaluates an experiment in which individuals in rural Malawi were randomly assigned monetary incentives to learn their HIV results after being tested. Distance to the HIV results centers was also randomly assigned. Without any incentive, 34 percent of the participants learned their HIV results. However, even the smallest incentive doubled that share. Using the randomly assigned incentives and distance from results centers as instruments for the knowledge of HIV status, sexually active HIV-positive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
408
8
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(433 citation statements)
references
References 60 publications
13
408
8
4
Order By: Relevance
“…Patients who otherwise would not be likely to seek a diagnosis, would fail to pick up the test result or who would be likely to discontinue treatment prematurely due to the associated direct medical and non-medical costs are encouraged and enabled to pursue treatment because some of the expenses are covered or offset by the value of the transfer. While a study in Malawi has shown that small cash transfers can significantly increase the likelihood of people returning to pick up their HIV test result [40], a transfer may be easier to implement and justify once a patient is diagnosed and needs treatment for a period of at least 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who otherwise would not be likely to seek a diagnosis, would fail to pick up the test result or who would be likely to discontinue treatment prematurely due to the associated direct medical and non-medical costs are encouraged and enabled to pursue treatment because some of the expenses are covered or offset by the value of the transfer. While a study in Malawi has shown that small cash transfers can significantly increase the likelihood of people returning to pick up their HIV test result [40], a transfer may be easier to implement and justify once a patient is diagnosed and needs treatment for a period of at least 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have shown that uptake of preventive behaviours is very sensitive to small incentives that can play a role in promoting preventive health services. [16][17][18] …”
Section: Vaccinementioning
confidence: 99%
“…Workers who receive information that they are malaria negative respond with higher levels of physical activity. This provides complementary evidence that workers shift effort in response to health perceptions , and is further evidence of general behavioral responses to health information (see Madejewicz et al (2007), Jalan & Somanathan (2008), Thornton (2008), Dupas (2011), Cohen et al (2015, Gong (2014), Baird et al (2014)). …”
Section: Resultsmentioning
confidence: 63%